Infrared photodetectors based on reduced graphene oxide nanoparticles and graphene oxide - Ahmad, Harith; Tajdidzadeh, Mojgan; Thambiratnam, Kavintheran; Yasin, Moh (IOP Publishing, 2018)
Two photodiode (PD) designs incorporating graphene oxide (GO) and reduced graphene oxide (rGO) are proposed and fabricated. Both PDs have 50 mm thick silver electrodes deposited on the active area, and another electrode consisting of either GO or rGO nanoparticles (NPs). The GO and rGO NPs are deposited onto the p-type silicon substrate by the drop casting method. Both fabricated PDs show good sensitivity and quick responses under 974 nm laser illumination at 150 mW. The photoresponsivity values and external quantum efficiency of both photodetectors are measured to be approximately 800 μAw-1 and 0.12% for the GO based PD and 1.6 m Aw-1 and 0.20% for the rGO based PD. Both PDs also have response and recovery times of 114 μs and 276 μs as well as 11 μs and 678 μs for the GO and rGO based PDs respectively. The proposed PDs would have significant applications in many optoelectronic devices as well as nanoelectronics.